2011
DOI: 10.5897/ijps11.1007
|View full text |Cite
|
Sign up to set email alerts
|

A research on work accidents in forest products industry in Duzce

Abstract: This study aimed at examining the work accidents and their possible causes experienced by the workers of the industry of forest products active in Duzce and their occupational lives, and determining the solutions suggested. In this study, a questionnaire method was used as a data gathering tool. The questionnaire used in the study composed of 4 main parts and 46 questions. In the forest products industry in Duzce, there are 3500 workers according to the 2010 data. It is required that a minimum of 250 workers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Similar results were presented by Enez et al [27]. Different results were obtained by Gedik and Korkut [28], who found that 77.7% of employees, in order to provide safety, use protective measures at the workplace, mainly gloves, masks, goggles, and helmets. In this study, it was also found that the older and more experienced the employees, the more rarely they used protective measures.…”
Section: Discussionsupporting
confidence: 78%
“…Similar results were presented by Enez et al [27]. Different results were obtained by Gedik and Korkut [28], who found that 77.7% of employees, in order to provide safety, use protective measures at the workplace, mainly gloves, masks, goggles, and helmets. In this study, it was also found that the older and more experienced the employees, the more rarely they used protective measures.…”
Section: Discussionsupporting
confidence: 78%
“…Accidents may happen due to several factors, such as carelessness of workers, inadequate skill or lack of occupational experience to operate heavy equipment, and low awareness towards occupational health and safety aspect. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Accidents may happen due to several factors, such as carelessness of workers, inadequate skill or lack of occupational experience to operate heavy equipment, and low awareness towards occupational health and safety aspect. 3,4 Despite technological advances that have resulted in a diverse range of timber harvesting machinery, 5 chainsaws are still widely used in forest operation due to their multifunctional use and low financial investment. 6 On the other hand, the use of chainsaws has been linked to the high accident rates in professional and non-professional work.…”
Section: Introductionmentioning
confidence: 99%